Sex differences in concussion symptoms of high school athletes - Frommer, L. J.; Gurka, K. K.; Cross, K. M.; Ingersoll, C. D.; Comstock, R. D.; Salib, S. A. (Journal of Athletic Training, 2011)
Context: More than 1.6 million sport-related concussions occur every year in the United States, affecting greater than 5% of all high school athletes who participate in contact sports. As more females participate in sports, understanding possible differences in concussion symptoms between sexes becomes more important.